Spatial evolution of the river valleys under the influence of active volcano: A case of Merapi volcanic plain - Ashari, Arif; Purwantara, Auhadi; Arif, Nursida; Widodo, Edi (Quaestiones Geographicae, 2021)
Merapi Volcano in Central Java, Indonesia, has a high eruption intensity that triggers landscape changes in the form of a river channel evolution. In this paper, the spatial change of river valleys under the influence of sediments deposition in the fluvio-volcanic system is investigated. The data were collected by employing observation, remote sensing image interpretation, literature study and documentation of data from several agencies. The data were analysed using the spatial approach supported by geographic information system (GIS) and remote sensing. The results show that there are many palaeochannels related to fluvio-volcanic processes from the southern to the western sectors of the Merapi volcanic foot. Palaeochannels are mainly distributed next to the main river valleys. This condition correlates with the contributions of the Merapi eruptions. The palaeochannel distribution patterns cluster radially following the distribution pattern of the river valleys. The process that plays the most important role in the evolution of palaeochannels is the deposition of lahar. In sum, this research shows that volcanic activities over a long period of time have provided great and important contributions that have driven the landform evolution. The various changes that occur also reveal the unique morphological characteristics, showing the influence of the volcanic processes.